Pengaruh Sistem Pengendalian Internal, Keadilan Organisasi Dan Moralitas Individu Terhadap Kecenderungan Kecurangan (Fraud): Studi Pada BPR Di Kecamatan Sukawati - Julia, Ni Made; Sudiana, I Wayan; Putra, I Putu Deddy Samtika (Hita Akuntansi dan Keuangan, 2022)
The aims of this study to analyze: (1) The Effect of Internal Control System on Fraud Tendency. (2) The Effect of Organizational Justice on Fraud Tendency. (3) The Influence of Individual Morality on the Fraud Tendency. The theory used in this research is from Fraud Triangel Theory. The population in this study were all active employees at BPR in Sukawati District. After selecting the sample using the Slovin formula, a sample of 84 respondents was obtained. The method of analysis of this study using multiple linear regression. The classical assumption test produces a regression model that does not occur multicollinearity and does not occur heteroscedasticity. The results of this study indicate that: (1) Internal Control System has a negative and significant effect on the tendency to fraud, (2) organizational justice has a significant effect on the tendency to fraud, (3) individual morality has a negative and significant effect on the tendency to fraud.